Planning and simulation of DRM digital radio technology using Single Frequency Network method for Indonesia - Musfirah; Gunawan, Dadang (Buletin Pos dan Telekomunikasi, 2024)
This study aims to design a digital radio network using a single-frequency network (SFN) and Digital Radio Mondiale (DRM) technology in Indonesia. The single frequency used is 87.1 MHz. Based on the ITU Radio Regulation, this frequency channel is still part of the broadcasting allocation for Region 3 and has not been used for analog radio in Indonesia. SFN design and simulation were carried out using existing analog transmitters owned by RRI to cover the entire territory of Indonesia. The simulation uses CHIRplus_BC software, which is based on recommendations, reports, and ITU-R publications on parameters and technical provisions of SFN. The technical provisions that are a limitation in SFN design are the maximum distance between transmitters of 75 km. However, the existing transmitter location of RRI transmitters is not evenly distributed throughout Indonesia, so not all transmitters can be used. Therefore, this design requires 3 scenarios in order to cover 95% of the population of Indonesia. The first condition in this plan is to use the existing transmitter sites owned by LPP RRI with a maximum distance of 75 km between the transmitter locations. The second condition is to use the transmitter sites owned by TVRI to cover the remaining blank spots in regions not covered by RRI's locations. If both of them still could not cover all regions in Indonesia, then it will need to add some new transmitters in blank spot locations. The simulation result showed that service in all regions in Indonesia requires at least 330 transmitters consisting of 153 existing RRI transmitters, 45 TVRI transmitters and 132 new transmitters with a settled technical parameter. To be able to cover all regions of Indonesia through SFN design, RRI still needs to build new transmitters as much as 40% of the total transmitters needed